The Influence of Organizational Culture, Work Motivation, and Work Experience on Employee Performance at the UPT Petapahan Health Center, Kampar Regency - Sabarahayu, Meysin Putri; Sasmita, Jumiati; Fitri, Kurniawaty (Journal Of Accounting Management Business And International Research, 2025)
This study aims to analyze the influence of organizational culture, work motivation, and work experience on the performance of employees at the Puskesmas UPT Petapahan in Kampar Regency. The data used in this study is primary data collected through questionnaires distributed to 42 employees of Puskesmas UPT Petapahan. The data analysis method used includes multiple linear regression analysis to test the influence of independent variables on the dependent variable using the SPSS test tool version 23. The results of the study indicate that organizational culture, work motivation, and work experience have a significant effect on employee performance. organizational culture has a positive and significant influence on employee peformance. work motivation has a negative and significant influence on employee performance. while work experience has a positive and significant influence on employee peformance.